Education at the Intersection of Globalization and Technology - Waller, Sharon; Waller, Lee; Mpofu, Vongai; Kurebwa, Mercy (IntechOpen, 2021)
Today's educators stand at the crossroads of globalization and technology. The world is rapidly shrinking. The workplace is being transformed before our very eyes. Technology is forever changing the way we perceive reality and the way we do business. Educators are required to equip students for a workplace that has yet to emerge. The skill sets of today's job market are often obsolete before students can enter the workplace. Now is the time for educators to rise to the challenges of our modern world. By embracing the vision of yesterday's practitioners and joining hands with tomorrow's practitioners, educators can transform our world and equip their students for the upward mobility and career flexibility required in tomorrow's workplace.